Issues in Canadian Geoscience. The Canadian Federation of Earth Sciences / Fédération Canadienne des Sciences de la Terre: 2008 Highlights - Kosters, Elisabeth (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2009)
SUMMARY The Canadian Geoscience Council (CGC) was reorganized into the Canadian Federation of Earth Sciences/ Fédération Canadienne des Sciences de la Terre (CFES/FCST) in the fall of 2006. This article highlights the activities of the new organization in 2008, the first year that real progress and renewal could be demonstrated. The organization aims to be the unified voice of earth science in Canada, using a multi-pronged approach along three lines: defragmentation of the Earth Science sector, outreach (to K-12 and the general public) and lobbying (to decision makers). We also published a Human Resources snapshot of our sector and are making progress toward creating one Canadian Geoscience Literature database.